E-conciliation vie de travail / vie hors travail : intervenir par le théâtre‑forum - Vincent Grosjean; Ophélie Morand; Béatrice Cahour; Marc-Éric Bobillier-Chaumon (Activités)
E-mail overload, a problem heightened by the combination of the smartphone and messaging, has various negative consequences, particularly in terms of work-life balance. Attempts to find solutions can take the form of company agreements or rely on individual strategies developed by the jobholders themselves. In this article, we explore a third solution, the collective discussion of what the workers themselves feel to be 'problematic'. With the help of a group of occupational physicians in a large company, a debate based on forum-theatre was developed and tested. Based on a thorough analysis of this case study, the article examines how the deployed method enabled a group of people that included managers to build a deep understanding of a complex problem and its possible solutions. The results show the benefits of the forum-theatre framework both for the group of people who wished to raise awareness of the importance of the problem and for the company members who were secondarily challenged by this issue.